JARINGAN SOSIAL DALAM KEHIDUPAN NELAYAN DI KEPENGHULUAN BAGAN PUNAK PESISIR KECAMATAN BANGKO BAGAN SIAPI-API KABUPATEN ROKAN HILIR - ", Sahrini; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the description of social networks, relationships and the influence of social networks on the level of welfare in fishermen's life in Kepenghuluan Bagan Punak Pesisir. This study uses an inferential quantitative approach. The population in this study were 255 fishermen in Kepenghuluan Bagan Punak Pesisir, with a sample of 69 people. The sampling technique used in this research is Cluster Random Sampling. The results showed that 72.5% were in the medium level category of social networks, 27.5% were in the high level category, and 0% were in the low category. Research Results The level of fishermen's welfare shows that 55 respondents (79.8%) belong to the Prosperous family I, 53 respondents (76.8%) belong to the prosperous family II and the prosperous family III also have the same frequency, namely in the prosperous family II. , 46 respondents belong to the prosperous family III +. The result of the Pearson product moment correlation test shows that the correlation coefficient between social network variables and the welfare level variable is 0.844 with the Sig. 0,000. Because of Sig. 0.000 <0.05, then the alternative hypothesis (Ha) in this study is accepted. There is a very strong and positive relationship between social networks and the level of welfare of fishermen in Kepenghuluan Bagan Punak Pesisir. The simple regression test results obtained the coefficient of determination (Rsquare) which is equal to 0.713. This means that the influence of social network variables on the level of welfare is 71.3%, while 28.7% is influenced by variables not examined in this study.Â Keywords: Fishermen, Social Networks, WelfareÂ